2001
DOI: 10.1038/nbt0901-856
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay of prostate-specific antigen (PSA) using microcantilevers

Abstract: Diagnosis and monitoring of complex diseases such as cancer require quantitative detection of multiple proteins. Recent work has shown that when specific biomolecular binding occurs on one surface of a microcantilever beam, intermolecular nanomechanics bend the cantilever, which can be optically detected. Although this label-free technique readily lends itself to formation of microcantilever arrays, what has remained unclear is the technologically critical issue of whether it is sufficiently specific and sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
624
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 963 publications
(649 citation statements)
references
References 29 publications
6
624
1
6
Order By: Relevance
“…As a result, proteomics is limited by the concentration sensitivity of existing technologies that are unable, despite the successful development of MS, 2-D-electrophoresis, multidimensional chromatography, and a variety of other methods, to overcome the CSL of 10 212 M (Table 1) [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…As a result, proteomics is limited by the concentration sensitivity of existing technologies that are unable, despite the successful development of MS, 2-D-electrophoresis, multidimensional chromatography, and a variety of other methods, to overcome the CSL of 10 212 M (Table 1) [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Кантилеверные сен соры позволяют определять белки, являющиеся маркерами различных заболеваний. Например, показана возможность детектирования простат специфического антигена -маркера заболеваний предстательной железы -на клинически значимом уровне концентраций [5]. В другой работе [6] опре делялась концентрация миоглобина, являюще гося маркером сердечно сосудистых заболеваний.…”
Section: области применения биосенсоров в зависимости от варианта интunclassified
“…Cantilever sensors allow to identify proteins that are markers of various diseases. For example, the possibility of detec tion of prostate specific antigen, a marker of prostate cancer, in clini cally significant concentrations was shown [5]. In another project [6] the concentration of myoglobin, which is a marker of cardiovascular dis eases, was determined.…”
Section: Applications Of Biosensors Depending On Types Of Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using a microscale cantilever, Hansen et al (2001) reported that it was possible to discriminate DNA single-nucleotide mismatches. In a separate study, Wu et al (2001) demonstrated the feasibility of the approach to quantify PSA at a clinically relevant concentration. Although both these studies were done using a microscale cantilever, it is not difficult to envisage a future where nanowires and nanotubes will function as the sensors (Zheng et al, 2005), offering the possibility of large-scale monitoring of the proteome or the transcriptome for subtle changes in the profile and relate it to the early stages of cancer progression.…”
Section: Nanotechnology and Biosensorsmentioning
confidence: 99%